Two new species of Telipogon (Orchidaceae: Oncidiinae) from Costa Rica - Bogarín Chaves, Diego Gerardo 1982-; Pupulin, Franco 1960-; Pérez Escobar, Oscar Alejandro (2024)
The Neotropical genus Telipogon (Oncidiinae), comprising approximately 250 species, exhibits remarkable species diversity in the humid, montane forests of southern Central America and the Tropical Andes. Telipogon, when broadly defined, encompasses both the large-flowered species that mimic tachinid flies and the small-flowered species formerly classified under Stellilabium. In Costa Rica, this genus includes 55 species, with 16 classified as small-flowered species. While the large-flowered species of Telipogon (in the strict sense) have been taxonomically revised, the small-flowered species have yet to be the subject of a thorough taxonomic revision. Our research aims to partially fill this gap by focusing on a comparative morphological analysis of two novel small-flowered Telipogon species. We describe and illustrate Telipogon lateritius and T. muntzii, both discovered in the humid mid-elevation forest of the Caribbean watershed in Cordillera de Talamanca, Costa Rica. Telipogon lateritius is notable for its distinctive brick-colored flowers, featuring sepals, petals, and lips striped in chestnut brown; the lateral sepals connate into a triangular-ovate synsepal, complemented by sparse, stiff pubescence at the base of the lip. Telipogon muntzii, although closely resembling T. anacristinae, differs in its unique olive-green flowers, sparse trichomes on the lip, narrowly oblong lateral lobes of the column, and a helmet-shaped median lobe of the column exclusively covered by simple trichomes. This study provides new additions for a future taxonomic revision of Telipogon in Costa Rica.
El género neotropical Telipogon (Oncidiinae), que comprende aproximadamente 250 especies, exhibe una notable diversidad de especies en los bosques húmedos montanos del sur de Centroamérica y los Andes tropicales. Telipogon, en sentido amplio, abarca tanto las especies de flores grandes que imitan a las moscas taquínidas como las especies de flores pequeñas anteriormente clasificadas en Stellilabium. En Costa Rica, este género incluye 55 especies, de las cuales 16 están clasificadas como especies de flores pequeñas. Mientras que las especies de Telipogon de flores grandes (en sentido estricto) han sido revisadas taxonómicamente, las especies de flores pequeñas aún no han sido objeto de una revisión taxonómica exhaustiva. Nuestra investigación tiene como objetivo llenar parcialmente este vacío centrándose en un análisis morfológico comparativo de dos nuevas especies de Telipogonde flores pequeñas. Describimos e ilustramos Telipogon lateritius y T. muntzii, ambos descubiertos en el bosque húmedo de elevación media de la cuenca del Caribe en la Cordillera de Talamanca, Costa Rica. Telipogon lateritiusse destaca por sus distintivas flores de color ladrillo, con sépalos, pétalos y labios con rayas de color marrón castaño, los sépalos laterales connados en un sinsépalo triangular-ovado, complementados con una pubescencia escasa y rígida en la base del labio. Telipogon muntzii, aunque similar a T. anacristinae, difiere por sus flores únicas de color verde oliva, escasos tricomas en el labelo, lóbulos laterales de la columna estrechamente oblongos y un lóbulo mediano de la columna en forma de casco cubierto exclusivamente por tricomas simples. Este estudio proporciona nuevas adiciones para una futura revisión taxonómica de Telipogon en Costa Rica.
Keywords: ORQUÍDEAS -- CLASIFICACIÓN -- COSTA RICA; ORQUIDEAS -- FENOLOGIA; PLANTAS ENDEMICAS; BOSQUES HUMEDOS